Stream Ecology and Self Purification: An Introduction, Second Edition - Spellman, Frank (CRC Press, 2009)
This new edition of a very successful standard reference is expanded and fully reworked. The book explains and quantifies the processes whereby streams cleanse themselves, reducing their pollutant load as a natural process. Mechanisms of purification in running waters have always been critical with regard to clearly identified pollution sources. This new edition explains the self-purifying function of streams and rivers in light of recent EPA rules on nonpoint pollutants and total maximum daily loads (TMDLs). It also covers basic concepts such as biological oxygen demand (BOD). Also new in this edition is an extended discussion of how streams originate and how they fit into the geomorphology of the earth and other water supply sources.